Regional Analysis: An Interindustry Model of Utah - Moore, Frederick T.; Petersen, James W. (The Review of Economics and Statistics, 1955)
R EGIONAL analysis has received an increasing amount of attention recently, a reflection in part of the growing volume of national macro-economic studies that point up the significance of regional compositions and regional patterns of behavior. This paper attempts to demonstrate the usefulness and flexibility of interindustry (or input-output) models for regional analysis. Specifically, the paper has three objectives: (i) to present an interindustry model for the state of Utah with a discussion of the problems both conceptual and empirical that arise in a model of this type; (2) to develop some measures for estimating the importance of individual industries in the regional economy via the calculation of income and employment multipliers; (3) to present some methods by which dynamic elements can be introduced into the static system. This is a necessary element if the model is to be used for the analysis of regional business cycles, industrial growth and technological change, or for the computation of period (that is, truncated) multipliers. The static model is useful in a number of ways, as we attempt to show, not the least of which is its usefulness as a social accounting device for the region; but, for more careful analyses of the problems mentioned above, a partially dynamic formulation is desirable.